Produção do espaço e transformações urbanas no litoral sul de João Pessoa - PB - Barbosa, Adauto Gomes (2006)
This present work has as its objective the analysis of transformations relating to the production processes in the Southern littoral urban space of the city of João Pessoa PB. The research estimated that the urban space is the product, means and condition of the society which produces it. The object-area of this inquiry is constituted of five districts: Altiplano Cabo Branco, Portal do Sol, Ponta do Seixas, Penha and Costa do Sol. The urban expansion which occurs in this area is characterized by the appearance of sufficient contradictory space phenomenona. On the other hand, the launching of real estate products such as the horizontal closed condominiums, directed towards the upper class, and the occurrence of areas of irregular occupation, inhabited by lower socioeconomic class and with a great lack of infrastructure and basic urban services, revealing the social contradictions. Due to this, processes such as auto-segregation and segregation imposed beyond the precarious and delinquent inclusion, has become the determining characteristic of this part of the city in analysis. The study also takes into account the appreciation of the new urban environmental zoning of Altiplano do Cabo Branco and from this moment on, start the discussion about the tendencies of urban expansion in this area, due to the interests and strategies of the real estate sector and the prominent role of the government in the current valorization process of urban soil of the area. The presence of residuals of agricultural businesses indicates a typical picture of the peri-urban areas configuring what we observe today at the Southern littoral of João Pessoa